COMPARISON OF MAGNETOTELLURIC TENSOR IMPEDANCE MODELS TO DETERMINE GEOELECTRIC STRIKE FOR 2-D MODELING IN RANTAU DEDAP GEOTHERMAL FIELD, SOUTH SUMATERA - Sakinah, Irfani
Magnetotelluric survey has been conducted in Rantau Dedap geothermal field, South Sumatera in 2008 which is consisted of 180 stations. Resistivity structure is achieved by 2-D modeling wherein resistivity varies in one horizontal direction and depth. The direction along which the resistivity is constant is known as the geoelectric strike. Geoelectric strike is known by doing impedance tensor analysis from MT data. This research uses four methods in impedance tensor analysis consisted of Swift, Bahr, Tipper, and Phase Tensor. Swift method assumed 2-D resistivity structure with added noise. Bahr proposed a more complex model with multi-dimensional heterogeneity embedded in 2-D regional structure. Phase Tensor method can be applied to various resistivity structure cases, geoelectric strike is obtained by calculating phase tensor which can preserve regional information. 90° ambiguity in impedance tensor analysis output can be solved by Tipper method which consider relation between vertical magnetic field component and horizontal magnetic field component. Another output of impedance tensor analysis is skewness parameter, which becomes deviation measure of data from 2- D model. Furthermore, MT data is rotated mathematically then 2-D modeling conducted using WinGLink software. Geoelectric strike in Rantau Dedap geothermal field is known oriented in N30°E and data fulfill 2-D model criteria until period 100 s according to skew value. 2-D modeling is conducted in 28 stations of profile oriented perpendicular to geoelectric strike, N30°E. 2-D model represents low resistivity layer (<12 Ohm.m) above high resistivity zone, >72 Ohm.m. In the midst of these zones, there is zone with resistivity value of 12-72 Ohm.m.